Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Agrário Integrado 2020 - MADER (República de Moçambique - Ministério da Agricultura e Desenvolvimento Rural Direcção de Planificação e Políticas (DPP), 2021)
O crescimento agrícola em Moçambique é uma fonte essencial para promover o crescimento económico do País em geral e das famílias rurais em particular. O Programa do Governo para o Sector Agrário, em harmonia com a política económica do País, orienta-se para o alcance de grandes objectivos estratégicos, nomeadamente: (1) Segurança Alimentar; (2) Aumento do Rendimento Familiar; (3) Criação de Emprego/Inclusão Social e (4) Aumento da Produção e Produtividade. Este documento ilustra, de forma simples e clara, a situação e a dinâmica da agricultura em Moçambique durante o ano de 2020. O Inquérito Agrário Integrado (IAI 2020), indica que existem no país cerca de 4.3 milhões de explorações agro-pecuárias, das quais 4.167.702 (97.8%) são pequenas, 93.183 (2%) são médias, e 873 (<1%) são grandes explorações. Do total de cerca de 4.3 milhões de explorações (Pequenas e Médias), cerca de 6.9% receberam informação ou conselho técnico de extensão, 39.9% tiveram acesso à informação sobre preços e 0.6% acesso à crédito. A área cultivada foi de cerca de 5.5 milhões de hectares, onde 5.5% das explorações utilizaram pesticidas nos seus campos, 8.8% usaram estrume, 7.8% utilizaram fertilizantes químicos e 9.1% usou a rega. As principais culturas em diversas explorações são o Milho, Arroz, Mapira, Amendoim Pequeno, Feijão Nhemba, Feijão Boer, Mandioca, Algodão e Canade-açúcar. Grande parte das explorações cultivam Milho (83.8%), 23.6% Amendoim Pequeno, 18.3% Mapira, 12 .8% Arroz e 3.8% Mexoeira. O IAI 2020, realizado pela primeira vez com referencial distrital, é um Marco Estatístico e principal fonte de dados do sector agro-pecuário, assim como marco amostral, pois fornece dados fiáveis desagregados até ao nível Distrital, para apoiar o processo de planificação e tomada de decisão a todos níveis, baseadas em evidências científicas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura; demographics / demografia

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Resultados Definitivos: Censo 2017 - Instituto Nacional de Estatística - INE (2019)
O Censo foi realizado em todo o País de 1 a 15 de Agosto de 2017.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Anuário Estatístico - Statistical Yearbook 2017 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2018)
À semelhança das edições anteriores, o Anuário Estatístico 2017 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Anuário Estatístico - Statistical Yearbook 2016 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2017)
O Anuário Estatístico 2016 é parte da série de publicações que o Instituto Nacional de Estatística leva aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2012-2016. O ano de 2016 foi crucial no âmbito da preparação do IV Recenseamento Geral da População e Habitação 2017. Seguindo as recomendações internacionais, em Outubro teve lugar o Censo Piloto, onde foi testada toda a máquina e produzidos os devidos ajustamentos metodológicos rumo ao Censo 2017.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Pobreza e Bem-Estar em Moçambique: Quarta Availação Nacional - Inquérito Ao Orçamento Familiar - Iof 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Pobreza e Bem-estar em Moçambique: Resumo da Quarta Availação Nacional - Inquérito ao Orçamento Familiar - IOF 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Moçambique Inquérito Demográfico e de Saúde 2003 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2005)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Subnational HDI - Global Data Lab - Iñaki Permanyer; Jeroen Smits (Global Data Lab - Nijmegen Center for Economics (NiCE), Institute for Management Research, Radboud University)
Subnational Human Development Index - Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia

Mozambique HDI Data - UNDP
Access and explore human development data for 191 countries and territories worldwide. Select Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia